Adaptive approaches to reproductive management of high-yielding dairy cows under thermal stress - Pryshedko, Vladimir M.; Pryshedko, V. M.; Pryshedko, V.; Prishedko, V.; Pryshed’ko, Vladimir; Pryshedko, Volodymyr; Pryshedko, Volodymyr Mykhailovych; Пришедько, Володимир Михайлович; Halaktenov, D. O.; Галактенов, Д. О.; Lesnovska, O. V.; Lesnovskay, O. V.; et al. (Stepan Gzhytskyi National University of Veterinary Medicine and Biotechnologies Lviv, 2026)
Heat stress represents a major constraint for reproductive efficiency in modern dairy herds, particularly in high-producing cows. The present study evaluated the influence of seasonal variation in the temperature–humidity index (THI) on the reproductive performance of Holstein cows. It assessed the effectiveness of hormonal synchro-nization protocols under thermal load. The research was conducted at the private agricultural enterprise “Fortuna” in the Chernihiv region, Ukraine. A total of 165 Holstein cows were divided into three groups according to milk productivity: 4500 to 6000 kg, 6000 to 7500 kg, and 7500 to 9000 kg per lactation. Seasonal dynamics of concep-tion rate and service period duration were analyzed in relation to monthly THI values. The results revealed a pronounced seasonal pattern of reproductive performance. During thermoneutral periods in spring and autumn, the conception rate ranged from 44.1 to 56.2 percent. In contrast, during the summer months, when THI ranged from 74 to 79 units, fertility declined sharply to 20.1-31.9 percent. The negative impact of heat stress was most evident in high-yielding cows, where conception rate during the summer period was 2.8 times lower than the autumn peak, and the service period increased by 18 to 49 days. More than 61 percent of cows in this Group exceeded a 100-day service period, indicating substantial reproductive maladaptation under thermal stress. Application of hormonal synchronization protocols improved reproductive outcomes during periods of elevated environmental temperature. The Double Ovsynch protocol demonstrated greater efficiency than the standard Ovsynch scheme, increasing conception rate in high-yielding cows by 8.4 % during the summer period. The results indicate that thermal stress induces metabolic and endocrine disturbances that impair follicular development and reduce reproductive efficien-cy. Overall, the findings demonstrate that effective reproductive management under conditions of increasing climatic pressure requires the combined use of reproductive biotechnologies and improved environmental man-agement. Integration of hormonal synchronization protocols with strategies to reduce metabolic and thermal stress represents an important approach for maintaining fertility in high-producing dairy herds. Тепловий стрес є одним із головних чинників, що обмежують ефективність відтворення в сучасних молочних стадах, особливо у високопродуктивних корів. У цьому дослідженні оцінено вплив сезонних коливань температурно-вологісного індексу (THI) на показники відтворення корів голштинської породи. Було визначено ефективність протоколів гормональної синхронізації в умовах теплового навантаження. Дослідження проводили у ПСП «Фортуна» Чернігівської області, Україна. Загалом 165 корів голштинської породи було розподілено на три групи відповідно до рівня молочної продуктивності: від 4500 до 6000 кг, від 6000 до 7500 кг та від 7500 до 9000 кг молока за лактацію. Проаналізовано сезонну динаміку сервіс-періоду та відсотку заплідненості залежно від щомісячних значень THI. Результати свідчать про виражену сезонну закономірність показників відтворення. У термонейтральні періоди (навесні та восени) відсоток заплідненості коливався в межах 44,1–56,2 %. Натомість у літні місяці, коли значення THI становили 74–79 одиниць, рівень фертильності різко знижувався до 20,1–31,9 %. Негативний вплив теплового стресу був найбільш вираженим у високопродуктивних корів: у літній період відсоток їх заплідненості був у 2,8 раза нижчим порівняно з осіннім піком, а тривалість сервіс-періоду збільшилася на 18–49 днів. Понад 61 % корів цієї групи мали сервіс-період тривалістю понад 100 днів, що вказує на суттєву репродуктивну дезадаптацію в умовах теплового стресу. Застосування протоколів гормональної синхронізації дозволило покращити результати відтворення в періоди підвищених температур навколишнього середовища. Протокол Double Ovsynch продемонстрував вищу ефективність порівняно зі стандартною схемою Ovsynch, підвищивши відсоток заплідненості високопродуктивних корів у літній період на 8,4 %. Отримані результати вказують на те, що тепловий стрес викликає метаболічні та ендокринні порушення, які погіршують розвиток фолікулів і знижують ефективність відтворення. Загалом, результати дослідження доводять, що ефективне управління відтворенням в умовах зростаючого кліматичного тиску потребує поєднання репродуктивних біотехнологій та покращення умов утримання тварин. Інтеграція протоколів гормональної синхронізації зі стратегіями зниження метаболічного та теплового стресу є важливим підходом для підтримання фертильності у високопродуктивних молочних стадах.
Адаптивні підходи в управлінні відтворенням високопродуктивних молочних корів в умовах теплового стресу
Пришедько Володимир Михайлович https://orcid.org/0000-0002-7324-5458 Лесновська Олена Володимирівна https://orcid.org/0000-0002-9027-6734 Галузіна Людмила Ігорівна http://orcid.org/0000-0003-0478-0027 Шкваря Микола Миколайович https://orcid.org/0000-0001-7279-3642 Милостивий Роман Васильович https://orcid.org/0000-0002-4450-8813
Keywords: Holstein cows; корови голштинської породи; temperature–humidity index; температурно-вологісний індекс; heat stress; тепловий стрес; conception rate; відсоток заплідненості; hormonal synchronization; гормональна синхронізація; reproductive management; управління відтворенням